2014
DOI: 10.1039/c3cp53047g
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale resolution scanning thermal microscopy using carbon nanotube tipped thermal probes

Abstract: We present a new concept of scanning thermal nanoprobe that utilizes the extreme thermal conductance of a carbon nanotube (CNT) to channel heat between the probe and the sample. The integration of CNT in scanning thermal microscopy (SThM) overcomes the main drawbacks of standard SThM probes, where the low thermal conductance of the apex SThM probe is the main limiting factor. The integration of CNT (CNT-SThM) extends SThM sensitivity to thermal transport measurement in higher thermal conductivity materials suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 56 publications
(101 reference statements)
0
24
0
Order By: Relevance
“…Kim et al [9] reported a ⇠ 10 nm spatial resolution and a temperature resolution of ⇠ 15 mK using a customized AFM probe with an integrated nanoscale thermocouple in an ultra-high vacuum environment. By attaching a carbon nanotube to the tip of a conventional SThM probe and working under vacuum, Tovee et al [10], [11] demonstrated a higher sensitivity to heat transport and spatial resolution (20-30 nm) compared to standard probes. Such improvements are well suited for the study of nanoscale thermal transport and will play an important role in understanding energy dissipation, phonon transport, and electron-phonon interactions in nanoscale electronic and photonics devices.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al [9] reported a ⇠ 10 nm spatial resolution and a temperature resolution of ⇠ 15 mK using a customized AFM probe with an integrated nanoscale thermocouple in an ultra-high vacuum environment. By attaching a carbon nanotube to the tip of a conventional SThM probe and working under vacuum, Tovee et al [10], [11] demonstrated a higher sensitivity to heat transport and spatial resolution (20-30 nm) compared to standard probes. Such improvements are well suited for the study of nanoscale thermal transport and will play an important role in understanding energy dissipation, phonon transport, and electron-phonon interactions in nanoscale electronic and photonics devices.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, a better resolution has been claimed for the silicon probes, 37 but the heater is farther from the sample and our AFM has been optimized for the Pd probes that we adopted. Another possibility to enhance the resolution, could be to attach a carbon nanotube to the probe, as it has been done by Tovee et al 38 This would be interesting but rather beyond the scope of this paper where we are more interested in a reliable method for determining the thermal properties of 2D materials for heat injection along the cross-plane direction.…”
Section: Methodsmentioning
confidence: 99%
“…A 30 nm spatial resolution was reported by Tovee et al on few-layer graphene by using carbon nanotube tipped thermal probes. 38 K. Yoon et al 39 quantitatively determined the thermal conductivity of suspended graphene by using the so-called null-point SThM that employs a thermocouple as the thermal probe. In this work and in others, 40 however, the authors do not usually report thermal maps but only line scans.…”
Section: Introductionmentioning
confidence: 99%
“…The use of AFM for the high resolution imaging of materials surfaces has become increasingly common place in a wide range of subject areas, including biosciences and engineering 16 . Recent technological advancements make it possible to learn more about a sample than just its topography, and properties such as chemical composition, nanomechanics, thermal conductivity, elasticity and the Young's Modulus can all be determined 1,2,[17][18][19][20][21][22][23] . The aim of this PhD has been to apply more well known, and also bespoke, AFM methods to the peptide Amyloid beta 1:42 (Aβ1:42), the main pathogenic component of Alzheimer's disease (AD), with the hope of elucidating more about its nanostructure, assembly, dynamics and interaction with potential pharmaceuticals.…”
Section: 1mentioning
confidence: 99%
“…The SThM AFM system previously used at Lancaster University 22,23,35,188,252 features and therefore more care must be taken when making determinations from these results as the higher the sensor is from the substrate, the higher the temperature and resulting signal (reflected as brighter contrast in the images). SThM imaging is also affected by the size of the contact area, increased roughness and contact of the sample along the side of the cantilever (thus leading to a higher contact area) and therefore increased heat flow and a lower signal.…”
Section: Scanning Thermal Microscopy Nanoscale Mapping Of Thermal Conmentioning
confidence: 99%